2017
DOI: 10.3847/2041-8213/aa96a1
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Small-scale Turbulent Dynamo by Large-scale Shear

Abstract: Small-scale dynamos are ubiquitous in a broad range of turbulent flows with large-scale shear, ranging from solar and galactic magnetism to accretion disks, cosmology and structure formation. Using high-resolution direct numerical simulations we show that in non-helically forced turbulence with zero mean magnetic field, large-scale shear supports small-scale dynamo action, i.e., the dynamo growth rate increases with shear and shear enhances or even produces turbulence, which, in turn, further increases the dyn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Comparing equations (1) and (2) we see that this condition is met in the case of turbulence produced by jetinflated bubbles. Singh et al (2017) confirmed the finding of Kolokolov et al (2011) that the linear shear increases the small-scale dynamo growth rate. In their simulation Singh et al (2017) find that the fluctuating magnetic field growth rate increase as γ ∝ |S|.…”
Section: The Jet-driven Dynamo (Jedd)supporting
confidence: 78%
See 4 more Smart Citations
“…Comparing equations (1) and (2) we see that this condition is met in the case of turbulence produced by jetinflated bubbles. Singh et al (2017) confirmed the finding of Kolokolov et al (2011) that the linear shear increases the small-scale dynamo growth rate. In their simulation Singh et al (2017) find that the fluctuating magnetic field growth rate increase as γ ∝ |S|.…”
Section: The Jet-driven Dynamo (Jedd)supporting
confidence: 78%
“…Singh et al (2017) confirmed the finding of Kolokolov et al (2011) that the linear shear increases the small-scale dynamo growth rate. In their simulation Singh et al (2017) find that the fluctuating magnetic field growth rate increase as γ ∝ |S|. For S L = 0.009c s k f , where c s is the sound speed and k f = 2π/λ f is wave number of the velocity fluctuations of the turbulence, Singh et al (2017) find that the magnetic field reaches equipartition (where the magnetic pressure is about equal to the turbulent pressure) at a time of τ eq ≃ 190(k f u rms ) −1 .…”
Section: The Jet-driven Dynamo (Jedd)supporting
confidence: 78%
See 3 more Smart Citations